Chimerism-Based Experimental Models for Tolerance Induction in Vascularized Composite Allografts: Cleveland Clinic Research Experience - Maria Siemionow; Aleksandra Klimczak (Clinical and Developmental Immunology)
The preclinical experimental models of vascularized composite allografts (VCAs) have been rapidly developed for the assessment of immunomodulatory protocols for clinical application. Recently, researchers have focused on immunomodulatory protocols which overcome the immunologic barrier between the allogeneic donor and recipient and may lead to tolerance induction. In order to test the feasibility of chimerism induction, experimental VCAs have been performed in different models including rodents, large animals, and nonhuman primates. These models differ in the complexity of transplanted tissue and in their responses to immunomodulatory protocols. In most applications, VCA contains multiple-tissue components; however, each individual component of CTA possesses unique immunologic characteristics that ultimately contribute to the chimerism induction and successful outcome of the VCA. Heterogenic character and complexity of tissue components in different VCA models determine the quality and robustness of donor-specific chimerism. As introduced in experimental studies, variable immunomodulatory options have been studied to achieve tolerance to VCA in rodents and large animal models allowing for widespread application in clinic. In this paper, based on our own experience, we have analyzed the current knowledge of tolerance-inducing strategies via chimerism induction in VCA experimental models in the context of immunomodulatory protocols and VCA complexity and their relevance and applicability to clinical practice.